Reliability of the International Spinal Cord Injury Upper Extremity Basic Data Set - S. Tongprasert (2018)
© 2018 International Spinal Cord Society Study design: It is a psychometrics study. Objective: To assess the inter-rater reliability of the International Spinal Cord Injury Upper Extremity Basic Data Set (ISCI-UE). Setting: Maharaj Nakorn Chiang Mai Hospital, Chiang Mai, Thailand. Methods: Individuals with subacute and chronic cervical spinal cord injury (SCI) were recruited. One examiner rated five parts of the ISCI-UE, including the ability to reach and grasp, the shoulder function classification, utilization of adaptive devices used to enhance upper-extremity function, complications affecting upper-extremity function, and upper extremity/hand reconstructive surgery. A second blinded examiner repeated the procedures within 1 day. Quadratic weighted kappa was calculated to determine the inter-rater reliability. Results: Sixty participants were included in the study. Fifty-two patients were men, and the mean (SD) age of participants was 42.9 (14.3) years. The median (interquartile range) time since injury was 9.5 (1–53) months. A total of 117 upper limbs were assessed. The inter-rater reliability was substantial, with almost perfect agreement in all items (ability to reach and grasp = 0.98; shoulder function classification = 0.97; use of assistive devices = 0.89; complications = 0.74; and surgery = 1). Conclusion: The International Spinal Cord Injury Upper Extremity Basic Data Set (ISCI-UE) has very good inter-rater reliability for evaluating individuals with cervical SCI.